TMF1 is upregulated by insulin and is required for a sustained glucose homeostasis. Issue 2 (21st January 2021) - Rahimi, Roni; Malek, Israel; Lerrer‐Goldshtein, Tali; Elkis, Yoav; Shoval, Irit; Jacob, Avi; Shpungin, Sally; Nir, Uri
Abstract: Insulin‐regulated glucose homeostasis is a critical and intricate physiological process, of which not all regulatory components have been deciphered. One of the key players in modulating glucose uptake by cells is the glucose transporter‐GLUT4. In this study, we aimed to explore the regulatory role of the trans‐Golgi‐associated protein‐TATA Element Modulatory Factor (TMF1) in the GLUT4 mediated, insulin‐directed glucose uptake. By establishing and using TMF1−/− myoblasts and mice, we examined the effect of TMF1 absence on the insulin driven functioning of GLUT4. We show that TMF1 is upregulated by insulin in myoblasts, and is essential for the formation of insulin responsive, glucose transporter GLUT4‐containing vesicles. Absence of TMF1 leads to the retention of GLUT4 in perinuclear compartments, and to severe impairment of insulin‐stimulated GLUT4 trafficking throughout the cytoplasm and to the cell plasma membrane. Accordingly, glucose uptake is impaired in TMF1−/− cells, and TMF1−/− mice are hyperglycemic. This is reflected by the mice impaired blood glucose clearance and increased blood glucose level. Correspondingly, TMF1−/− animals are leaner than their normal littermates. Thus, TMF1 is a novel effector of insulin‐regulated glucose homeostasis, and dys‐functioning of this protein may contribute to the onset of a diabetes‐like disorder.